The role of race in teacher education standards for mathematics: what is missing and why it matters. Issue 1 (2nd January 2019) - Ketner, Amanda L.
ABSTRACT: With a teaching force that is predominately White educating a growing proportion of students of color, there is a pressing concern in the United States to address how teachers are prepared to confront the racial realities of their classrooms. By critiquing general and mathematics teacher education standards, this paper finds that inadequate attention is paid to race in the existing standards. Highlighting the need to explicitly discuss the structural racism endemic in mathematics, education, and society affecting students of color, the argument is made to alter teacher educations standards to ultimately produce a workforce that is capable of understanding how to effectively teach students of color who have historically been marginalized in education.